Neoliberalism and the problem of migrant workers (International relations and international law Journal, 2020)
This article considers the process of neoliberalism and globalization causing international migration, and the status of migrant workers in their countries of residence around the world, including Korea. According to the results of research, first, globalization guarantees maximum movement of capital, whereas human free movement is suppressing as much as possible. The labor market pursued by neoliberalism has focused on the flexibility of labor. The flexibility of the production system and the flexibility of the labor market have forced workers in many parts of the world into a chaotic state suffering from job insecurity, competition, and performance. Migrant workers are subjected to labor exploitation as they are treated with inequality and discrimination compared to local workers in their countries of residence.Second, under the neoliberalistic economic system, migrant workers are forced to live as wage slaves by the logic of capital’s power, foreign discrimination in residential countries, and the scapegoats of anti-immigration sentiment. Most immigrants are politically, economically, and socially unprotected from their home countries, and are given status as people who will return to their home countries after providing only a certain period of labor. In particular, the guarantee of labor is perfunctory for migrant workers, the de facto workplace cannot be moved, and the migrant workers can be sent out of the country. Third, globalization, driven by deregulation and new technologies based on past laissez-faire ideology, has led to income inequality, in which wealth is concentrated only in certain groups of capitalists.The Universal Declaration of Human Rights declares freedom of migration as one of the fundamental human rights. The Convention on the Rights of Labor Migrants has not yet been signed by countries that actively host labor migrants. OECD countries call for the elimination of the negative aspects of globalization and neoliberalism through improved international standards and norms and international cooperation. For both sending and receiving countries, migration should be planned and modified in such a way as to minimize negative factors and maximize benefits.